Integrating the Traditional Game Bentengan into Physical Education Learning to Enhance Students’ Cooperative Skills at SMAN 2 Tanjung Jabung Barat - Firna Yuniamanda; Hendri Munar; Tri Bayu Norito; Reza Hadinata (Athena: Physical Education and Sports Journal, 2026)
The present study investigates the implementation of the traditional game Bentengan in physical education learning and its influence on students’ cooperative skills. The research applied a quantitative descriptive approach involving 24 twelfth-grade students of SMAN 2 Tanjung Jabung Barat selected through purposive sampling. Data were collected through a cooperation questionnaire and an observation sheet covering five main indicators: active participation, communication, group responsibility, mutual respect, and mutual assistance. The data were analyzed descriptively using percentage calculations and classified into four levels: very good, good, fair, and poor. The results showed that the integration of Bentengan effectively enhanced students’ cooperation in PJOK learning, as seen through their increased participation, communication, and responsibility within the group. Furthermore, traditional game–based learning fosters mutual cooperation, sportsmanship, and a more interactive and meaningful learning atmosphere.